Serine protease inhibitors N-alpha-tosyl-L-lysinyl-chloromethylketone (TLCK) and N-tosyl-L-phenylalaninyl-chloromethylketone (TPCK) are potent inhibitors of activated caspase proteases - Frydrych, Ivo; Mlejnek, Petr (Journal of cellular biochemistry, 2008)
Serine protease inhibitors N-alpha-tosyl-L-lysinyl-chloromethylketone (TLCK) and N-tosyl-L-phenylalaninyl-chloromethylketone (TPCK) exhibit multiple effects on cell death pathways in mammalian cells. Thus, they are able to induce apoptosis by itself or promote cell death induced by other cytotoxic stimuli [King et al., 2004; Murn et al., 2004]. On the other hand, TLCK and TPCK were reported to prevent apoptosis by inhibiting the processing of caspases in response to some cell death inducing stimuli [Stefanis et al., 1997; Jones et al., 1998]. We observed that the pretreatment of HL-60 cells with TLCK or TPCK diminished caspases 3 and -7 (DEVDase) and caspase-6 (VEIDase) activity in response to various cell death inducing stimuli such as staurosporine (STS), etoposide (ETP), or N6-(2-isopentenyl)adenosine. In addition, TLCK but not TPCK inhibited collapse of mitochondrial transmembrane potential Delta Psi m (delta psi) in dying HL-60 cells. Such effects used to be considered as protective, however, the protection was only presumable since neither TLCK nor TPCK actually prevented cells from death. Our results further indicated that serine protease inhibitors TLCK and particularly TPCK acted as efficient direct inhibitors of mature caspases. Indeed, experiments with human recombinant caspases provided unequivocal evidence that TLCK and TPCK are very potent but non-specific inhibitors of activated caspases, namely caspases 3, -6, and -7. Interestingly, TPCK exhibited similar efficiency towards human recombinant caspases to that found for panspecific caspase inhibitor Boc-D-CMK. Such properties of TLCK and TPCK, previously considered as specific inhibitors of serine proteases, might offer novel consistent explanation for several protective or protective-like effects on apoptotic cells.
Keywords: tosyllysinchlormethylketon; inhibitory serinových proteinas; Recombinant Proteins; HL-60 buňky; Serine Proteinase Inhibitors; tosylfenylalanylchlormethylketon; inhibitory kaspas; Caspases; rekombinantní proteiny; kaspasy; Caspase Inhibitors; Tosylphenylalanyl Chloromethyl Ketone; lidé; HL-60 Cells; Humans; Tosyllysine Chloromethyl Ketone; apoptóza; membránový potenciál mitochondrií; Membrane Potential, Mitochondrial; Apoptosis